Physical but not cognitive demand of an exercise bout influences subsequent affective inhibition - Manuel Mücke; Antonella Greco; Tabea Müller; Markus Gerber; Uwe Pühse; Sebastian Ludyga (Current Issues in Sport Science, 2023)
Background